University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 3 - Section 3.3 - Differentiation Rules - Exercises - Page 136: 22



Work Step by Step

We are given that $w=(2x-7)^{-1}(x+5)$ $\implies w=\frac{x+5}{2x-7}$ Differentiating both sides and applying the quotient rule, we obtain: $\frac{dw}{dx}=\frac{(2x-7)(x+5)^{\prime}-(x+5)(2x-7)^{\prime}}{(2x-7)^2}$ $\implies \frac{dw}{dx}=\frac{(2x-7)(1)-(x+5)(2)}{(2x-7)^2} $ $\implies \frac{dw}{dx}=\frac{2x-7-2x-10}{(2x-7)^2}$ $\implies \frac{dw}{dx}=-\frac{17}{(2x-7)^2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.